Effect Of Herbicides On The Growth, Yield Components And Yield Of BR11 Paddy (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Eleven treatments with three herbicides were applied on BR11 paddy field to control weeds and also to study the growth, yield components and yield. The effect of herbicides was found to be positive in controlling the weed species and in increasing the yield components and yield. The maximum number and length of tillers, length of panicle, area of flag leaves, number and percentage of filled grains, grain and straw yield per hectare were found at T3 when normal dose of Rifit 500 EC was applied. Different doses of Machete 5G were also found effective in controlling weeds and increasing in yield. J. Asiat. Soc. Bangladesh, Sci. 39(1): 21-26, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16029